Limitation des émissions de GES de l’agriculture et séquestration de carbone via l’agriculture - Moussadek, Rachid (2023)
Reducing the carbon footprint of agro-industry , mainly by Limiting GHG emissions from agriculture and carbon sequestration through agriculture